Molecular analysis of Phytophthora diversity in nursery‐grown ornamental and fruit plants. (14th March 2015) - Prigigallo, M. I.; Mosca, S.; Cacciola, S. O.; Cooke, D. E. L.; Schena, L.
Abstract : The genetic diversity of Phytophthora spp. was investigated in potted ornamental and fruit tree species. A metabarcoding approach was used, based on a semi‐nested PCR with Phytophthora genus‐specific primers targeting the ITS1 region of the rDNA. More than 50 ITS1 sequence types representing at least 15 distinct Phytophthora taxa were detected. Nine had ITS sequences that grouped them in defined taxonomic groups ( P. nicotianae, P. citrophthora, P. meadii, P . taxon Pgchlamydo, P. cinnamomi, P. parvispora, P. cambivora, P. niederhauserii and P. lateralis ) whereas three phylotypes were associated to two or more taxa ( P. citricola taxon E or III; P. pseudosyringae, P. ilicis or P. nemorosa ; and P. cryptogea, P. erythroseptica, P. himalayensis or P . sp. ' kelmania ') that can be challenging to resolve with ITS1 sequences alone. Three additional phylotypes were considered as representatives of novel Phytophthora taxa and defined as P. meadii ‐like, P. cinnamomi ‐like and P. niederhauserii ‐like. Furthermore, the analyses highlighted a very complex assemblage of Phytophthora taxa in ornamental nurseries within a limited geographic area and provided some indications of structure amongst populations of P. nicotianae (the most prevalent taxon) and other taxa. Data revealed new host–pathogen combinations, evidence of new species previously unreported in Italy ( P. lateralis ) or Europe ( P. meadii ) and phylotypes representative of species that remain to be taxonomically defined. Furthermore, the results reinforced the primary role of plant nurseries in favouring the introduction, dissemination and evolution of Phytophthora species.